The response of sugar beet rhizosphere micro-ecological environment to continuous cropping - Cui, Rufei; Geng, Gui; Wang, Gang; Stevanato, Piergiorgio; Dong, Yinzhuang; Li, Tai; Yu, Lihua; Wang, Yuguang (Frontiers in Microbiology, 2022)
Continuous cropping can lead to increased soil-borne diseases of sugar beet (Beta vulgaris L.), resulting in a reduction in its yield quality. However, our understanding of the influence of continuous cropping on sugar beet-associated microbial community is limited and their interactions remain unclear. Here, we described and analyzed microbial diversity (N =30) from three sugar beet belowground compartments (bulk soil, rhizosphere soil, and beetroot) using 16S rRNA and ITS sequencing. The continuous cropping showed lower bacterial alpha diversity in three belowground compartments and higher fungal alpha diversity in roots compared to the non-continuous cropping. There were significant differences in fungal community composition between the two groups. Compared with non-continuous cropping, continuous cropping increased the relative abundance of potentially pathogenic fungi such as Tausonia, Gilbellulopsis and Fusarium, but decreased the relative abundance of Olpidium. The fungal flora in the three compartments displayed different keystone taxa. Fungi were more closely related to environmental factors than bacteria. Overall, changes in microbial diversity and composition under continuous cropping were more pronounced in the fungal communities, and the results of the study could guide development strategies to mitigate continuous crop adversity.